Fairness of the NPD partnership's financial distribution pie. Issue 5 (4th June 2019) - Wölfel, Joachim; Grosse-Ruyken, Pan Theo
Abstract : Purpose: Industry practice shows that buyer-supplier partnerships are negatively influenced by zero-sum pie-sharing competition. Interfirm rivalry vis-à-vis a fair financial distribution of the mutually generated partnership pie is a growing source of concern for firms because fairness has a direct effect on the competitiveness of a partnership. This study aims to examine the consequences of fairness in pie-sharing within buyer-supplier new product development (NPD) partnerships on product-innovation, product-quality and product-cost, as well as the mediating role of opportunism. Design/methodology/approach: The empirical analyses are grounded on data from 147 NPD partnerships between Tier-1 suppliers and automotive manufacturers, using structural equation modeling with SPSS AMOS. Findings: Findings indicate that pie-sharing fairness significantly influences the partnership's ability to increase NPD effectiveness and efficiency. Moreover, unfairness in sharing the mutual pie showed to promote harmful opportunism, which negatively mediates the relationship between pie-sharing fairness and NPD performance. To control partners' fairness perception in the first place, the analysis revealed three factors that affect pie-sharing fairness significantly, i.e. relationship induced financial performance, behavioral tension and interfirm dependency. Originality/value: Exchange relationships are built on economic and social components, both of which can be combined within the construct of pie-sharing fairness. Firms must take an interest in their exchange partner's equitable share of the mutually generated partnership pie, as pie-sharing fairness can be used to promote determinants of effectiveness and efficiency of their mutual NPD project. In a two-sided mutually contingent exchange behavior, the firm's own welfare must be regarded as an interorganizational overlap with the partner's, which can be optimized only by mutual efforts.